ORGANIZATIONAL TRUST IN NEW RENEWABLE ENERGY POLICY IMPLEMENTATION IN INDONESIA - Muhammad ikramullah Akmal (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
Implementation of new renewable energy policies is an important issue in climate change. In its implementation, trust between organizations is needed in achieving effective policy performance, considering that the policy is a cross-sectoral policy. This study uses a qualitative approach, data collection methods include observation, in-depth interviews and documentation studies. The informants in this study include cross-sectoral policy makers where the key informants are in the Ministry of Energy and Mineral Resources. Data sources include primary and secondary data. Data analysis using interactive data analysis. Where these various stakeholders have the ability and can be relied upon in managing new and renewable energy in Indonesia but still need to be improved. Where is the obedience then? Agreement designed to implement new renewable energy policies in Indonesia. Related to the motives of these stakeholders, normatively they have a common interest, namely to increase the production of new and renewable energy by starting to abandon conventional energy. Finalist the commitment and political will of the stakeholders required to be consistent in implementing new renewable energy policies.